A Review of Health Workers' Preparedness in Flood Disaster Management at Rantau Selamat Public Health Center, East Aceh Regency - Fitrina Ghaitsa; Harvina Sawitri; Wheny Utariningsih (Jurnal Ilmu Kedokteran dan Kesehatan Indonesia, 2025)
Health personnel play a crucial role in delivering health services, including disaster management. In Indonesia, floods are the most frequent type of disaster, with East Aceh District experiencing recurring floods that resulted in four fatalities between 2019 and 2022. Rantau Selamat Subdistrict is particularly vulnerable, making it essential for the local health center to function effectively as a frontline facility during flood events. This study aims to describe the preparedness of health workers in flood disaster management at the Rantau Selamat Health Center, East Aceh District. A descriptive research design with a cross-sectional approach was employed. Total sampling was used, involving 96 health workers. Data were collected through questionnaires. The results indicated that 95.8% of respondents had good knowledge and attitudes toward flood preparedness. However, disaster emergency response capacity was low among 62.5% of respondents, and 81.3% showed limited access to or awareness of an effective early warning system. In contrast, all respondents (100%) reported good readiness in terms of resource mobilization. In conclusion, most health workers demonstrated good knowledge, attitudes, and readiness in terms of resource and medication availability. However, weaknesses were identified in the emergency response plan and early warning system, indicating the need for strategic improvements to enhance overall preparedness for flood disaster management at the Rantau Selamat Health Center.